Biharmonic S-Curves According to Sabban Frame in Heisenberg Group Heis3 - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2013)
In this paper, we study biharmonic curves accordig to Sabban frame in the Heisenberg group Heis(3). We characterize the biharmonic curves in terms of their geodesic curvature and we prove that all of biharmonic curves are helices in the Heisenberg group Heis(3). Finally, we find out their explicit parametric equations according to Sabban Frame.
Keywords: Biharmonic curve; Heisenberg group; curvature; torsion